2019
DOI: 10.1101/841833
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temperature-related biodiversity change across temperate marine and terrestrial systems

Abstract: AbstractClimate change is reshaping global biodiversity as species respond to changing temperatures. However, the net effects of climate-driven species redistribution on local assemblage diversity remain unknown. Here, we relate trends in species richness and abundance from 21,500 terrestrial and marine assemblage time series across temperate regions (23.5-60.0°) to changes in air or sea surface temperature. We find a strong coupling between biodiversity and temperature changes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 53 publications
5
81
0
Order By: Relevance
“…Specifically, declines in insect abundance (regardless of their causes) appearto drive declines in bird population trends, with pronounced effects on insectivores and long-distance migrant species(Bowler, Heldbjerg, Fox, Jong, & Böhning-Gaese, 2019;Hallmann, Foppen, Turnhout, Kroon, & Jongejans, 2014).Our results highlight that changes in richness and abundance can be decoupled from each other(Schipper et al, 2016). In a similar vein,Antão et al (2019) reported how temperature-related trends in the number of individuals and number of species were not only decoupled, but exhibited geographically contrasting patterns during several decades of climate change. Such contrasting trends between richness and abundance might be explained by the ability of species to exploit microrefugia(Suggitt et al, 2018), allowing populations to persist in smaller pockets of suitable climate in the face of en-…”
supporting
confidence: 67%
See 1 more Smart Citation
“…Specifically, declines in insect abundance (regardless of their causes) appearto drive declines in bird population trends, with pronounced effects on insectivores and long-distance migrant species(Bowler, Heldbjerg, Fox, Jong, & Böhning-Gaese, 2019;Hallmann, Foppen, Turnhout, Kroon, & Jongejans, 2014).Our results highlight that changes in richness and abundance can be decoupled from each other(Schipper et al, 2016). In a similar vein,Antão et al (2019) reported how temperature-related trends in the number of individuals and number of species were not only decoupled, but exhibited geographically contrasting patterns during several decades of climate change. Such contrasting trends between richness and abundance might be explained by the ability of species to exploit microrefugia(Suggitt et al, 2018), allowing populations to persist in smaller pockets of suitable climate in the face of en-…”
supporting
confidence: 67%
“…Our results highlight that changes in richness and abundance can be decoupled from each other (Schipper et al, ). In a similar vein, Antão et al () reported how temperature‐related trends in the number of individuals and number of species were not only decoupled, but exhibited geographically contrasting patterns during several decades of climate change. Such contrasting trends between richness and abundance might be explained by the ability of species to exploit microrefugia (Suggitt et al, ), allowing populations to persist in smaller pockets of suitable climate in the face of environmental changes (Aalto, Riihimäki, Meineri, Hylander, & Luoto, ; Greiser, Meineri, Luoto, Ehrlén, & Hylander, ; Maclean, Suggitt, Wilson, Duffy, & Bennie, ; Meineri & Hylander, ).…”
Section: Discussionmentioning
confidence: 86%
“…Like all ecosystems on the planet, these assemblages are impacted by combinations of global stressors [ 17 ]. Specifically, BioTIME time series are affected by the ubiquitous climate change [ 18 ], marine data include locations affected by overfishing [ 19 ], and most of the range in forest loss found across the planet is covered by BioTIME [ 20 ]. The widespread compositional change detected within BioTIME assemblages is indicative of change captured by these data [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…With ocean acidification altering animal behavior and function [1,2] and temperatureinduced biodiversity changes in marine environments [3,4], new tools can expand efforts to track markers of climate change in more sensitive or previously unexplored areas of the ocean [5].…”
Section: Introductionmentioning
confidence: 99%